Is it time to include oxygen needs as an endpoint in clinical trials in patients with fibrosing interstitial lung disease? If so, how? - Jeffrey J Swigris; Kerri Aronson; Susan S Jacobs; Dawn Repola (BMJ Open Respiratory Research)
Many patients with fibrosing interstitial lung disease (fILD) will need to use supplemental oxygen (O2) to maintain normoxia at some point in their illness. If it is not needed at the time of diagnosis, then if fILD progresses—or if a comorbid condition like pulmonary hypertension develops—O2 will become necessary, often, initially, during exertion and all-too-often, eventually, at rest as well. But presumably, if all else remains stable, if fILD progression is halted or slowed, O2 needs follow in parallel. Despite perceived or unnoticed benefits of O2, and prescribers’ good intentions to improve patients’ sense of well-being, patients with fILD generally view O2 with frustration and fear, as it threatens their already-impaired quality of life. Because of how meaningful and impactful O2 is to the lives of patients with fILD, ‘O2 need’ is a critically important—and perhaps the most—patient-centred metric that should be considered for incorporation as an endpoint in therapeutic trials. It is unclear how this should be done, but in this paper, we offer some possible approaches that merit consideration.